Tuberous Sclerosis Complex Associated Neuropsychiatric Disorders and Parental Stress: Findings from a National, Prospective TSC Surveillance Study - Ebrahimi-Fakhari, Daniel; Hussong, Justine; Flotats-Bastardas, Marina; Ebrahimi-Fakhari, Darius; Zemlin, Michael; von Gontard, Alexander; Meyer, Sascha (Neuropediatrics, 2019)
Aim To assess the role of the TAND (tuberous sclerosis complex [TSC] associated neuropsychiatric disorders) checklist as a screening tool for neuropsychiatric pathology, to evaluate behavioral and psychiatric symptoms and related parental stress in children with TSC, and to analyze associations between parental stress, TAND findings, and TSC pathology.Method This is a prospective cohort study including 22 individuals from a national TSC surveillance study in Germany using demographic and clinical data, the TAND checklist, the Child Behavior Checklist (CBCL), and the Parenting Stress Index (PSI).Results Mean (standard deviation) age at follow-up was 4 years (3 years 9 months), and 13/22 of patients were male. Seventeen children had epilepsy (focal: 9; generalized: 4; infantile spasms: 4). Developmental delay was diagnosed in 12/22 patients. The most prevalent TAND items were anxiety and mood swings in 10/22 children. At least one TAND item was reported by 17/22 patients, internalizing symptoms by 10/22, and externalizing symptoms by 11/22. In contrast, only one patient had a clinically relevant score in the CBCL scales. Of 22 parents, 12 reported clinically relevant parental stress due to both child and parenting factors. Higher total parental stress was associated with a higher TAND externalizing score (r = 0.49; p = 0.028) and TAND total score (r = 0.51; p = 0.016), a higher CBCL total score (r = 0.59; p = 0.005), and the number of antiepileptic drugs (r = 0.50; p = 0.017). Developmental delay was correlated with child stress factors (r = 0.48; p = 0.023).Interpretation The TAND checklist appears to be a promising screening tool for neuropsychiatric problems in very young children with TSC. Parental stress in children with TSC is modified by TSC-related pathology, both neuropsychiatric and neurological.
Keywords: tuberous sclerosis complex; TAND; neuropsychiatric symptoms; parental stress; epilepsy; behavior